First report of the damaging pest Meloidogyne enterolobii parasitizing mulberry (Morus alba L.) in Vietnam - Nguyen, H D (Plant disease, 2024)
Mulberry (Morus alba L.) is highly important crop in Vietnam, playing a key role in the country's economy through sericulture, food supply, pharmaceuticals, and beverage industries (Nguyen et al., 2018; Rohela et al., 2020). Recently, many mulberry-growing areas in Lam Dong, Vietnam have reported severe symptoms associated with nematode infection, including yellowing leaves, stunted growth, and severe root galling, leading to a significant decline in mulberry productivity. From April to December 2022, twenty soil and root samples from mulberry-growing areas in Lam Dong (Da Teh: 11°28'48.11"N; 107°28'23.74"E elevation: 133m; Lam Ha 11°48'25.13"N; 108°14'7.13"E elevation: 848m) were collected to uncover the presence of Meloidogyne enterolobii parasitizing mulberry in Vietnam. One nematode population was randomly selected for characterizing in this study among analyzed nematode populations. Females were extracted from heavily galled roots (Fig. S1) from a single mulberry tree in Lam Dong, Vietnam, using a needle and forceps (Subbotin et al., 2021). The perineal patterns of adult females (n = 10) have an oval shape, with clearly visible phasmids, along with a prominently high and squared dorsal arch. The striae are smooth and coarse, while the perivulval region remains devoid of striae. The lateral lines appear indistinct, and the tail tip is easily observable. Morphometric measurements were as follows: body length = 585 ± 78 (464-724) µm, body width = 367 ± 75 (271-529) µm, neck length = 221.5 ± 30.7 (167-269.6) µm, stylet length = 13.1 ± 1.2 (11.4-15.1) µm, vulva-slit length 16.3±2.3 (10.4-18) µm, vulva-anus distance = 16.8±3.0 (11.4-18) µm, anus-tail tip distance = 10.3±2.1 (6.9-14.2) µm, interphasmidial distance = 15.9 ± 3.7 (10.3-23.4) µm. The morphology of this nematode population is highly in agreement with the original description of M. enterolobii (Yang & Eisenback, 1983). This population was also identified using the D2-D3 of 28S rRNA and 18S rRNA (Powers et al., 2017; Subbotin et al., 2006) regions. The D2-D3 of 28S rRNA sequences from this study (accession numbers: OR889633) exhibited 99.5-99.8% similarity to the sequences of M. enterolobii from GenBank (accession numbers: OR214950 and ON496981). While the 18S rRNA sequences (accession numbers: OR896547) showed 99.2-99.3% similarity to the sequences of M. enterolobii from GenBank (accession numbers: MZ955995, MZ531901, and MW488150). To carry out Koch's postulates, 2000 J2s from collected M. enterolobii egg masses (initial population) were inoculated on two-month-old plantlets of mulberry (n = 6), planted on 2L pots within a screenhouse, non-inoculated plantlets (n=6) served as negative controls. After 90 days post-inoculation, nematode reproduction factors (RF = final density (nematodes were extracted from the whole root system and corresponding soil samples (Subbotin et al., 2021)) / initial population) and root damage symptoms were evaluated. The inoculated plantlets exhibited consistent yellowing leaves, stunting, and root galling symptoms (Fig. S1), mirroring observations from the field, with an average RF of 11.5. Control plants displayed no symptoms. Root-knot nematodes extracted from the roots were identified as M. enterolobii through molecular analyses of D2-D3 of 28S and 18S rRNA regions (GenBank accession numbers: OR889634 (D2-D3 of 28S) and OR896548 (18S)), thereby confirming that mulberry acts as a host for M. enterolobii. Currently, this nematode has been reported to be associated with two different host plants, including guava (Trinh et al., 2022) and pomelo (Le et al., 2023). Our discovery marks the first documented case of Meloidogyne enterolobii parasitizing mulberry in Vietnam. While the impact on mulberry productivity remains to be really important for sericulture food supply, pharmaceuticals, and beverage industries; the aggressive nature of M. enterolobii, as observed in the field and confirmed by the screenhouse tests, raises concerns about potential economic losses in mulberry production. Therefore, further investigations are needed to assess the extent of M. enterolobii infestation in mulberry orchards and to develop effective control measures to safeguard the sustainability of mulberry cultivation in Vietnam